Knowledge, Learning and Innovation Research Insights on Cross-Sector Collaborations (Contributions to Management Science, 2018)
This book places knowledge, learning and innovation at the heart of cross-sector collaborations. Collaboration for innovation is a topic that has attracted widespread interest from academics, business strategists and government officials. To date the collaborations have focused on the performance management process and more specifically on how to encourage collaboration. However, businesses across the world are realizing that for cross-sector collaboration to be successful, it is necessary for firms to share knowledge and innovation through a process of learning. The book contributes to this by providing fresh insights into ways to stimulate cross-sector collaboration. It presents diverse methods and approaches to unify the dimensions of knowledge, learning and innovation and discusses how collaboration can be created, sustained, and expanded.